PENGEMBANGAN POP UP SCRAPBOOK UNTUK MENGUATKAN HISTORICAL COMPREHENSION PESERTA DIDIK SEKOLAH MENENGAH ATAS (Swarnadwipa, 2020)
The purpose of this research is to develop scrapbook pop-up media and describe its feasibility. The due diligence was carried out at the Pekalongan state high school 1. The method used in this study is the method of Research and Development (R&D). Adapted from the Sugiyono Level 1 model (produced a design but did not test). The stages of the research are potential problems, gathering information through observation, interviews, document collection, product design, media validation, media improvement, and the completion of scrapbook pop-up media products. The results of the research are the pop up scrapbook media designed in accordance with KI and KD 2013 curriculum in the subject of the struggle to realize Indonesian independence 1942-1945 to strengthen the historical compreshension (pemahaman sejarah) in students. The results of validation by material experts in phase 1 with a percentage of 81% (Very Strong), stage 2 of 95% (Very Strong), stage 1 and stage 2 increased by 14%. The results of validation by stage 1 media experts were 78% (Strong), stage 2 was 95% (Very Strong), stage 1 and stage 2 increased by 17%. The results of the responses of students by 97% (Very strong). It was concluded that the scrapbook pop-up media was worth trying out as a history learning media to strengthen students historical comprehension.